THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON ASN PERFORMANCE IN GOVERNMENT AGENCIES - Marwita Andarini; Wiwiek Andajani (RADJA PUBLIKA, 2025)
This study aims to examine the influence of transformational leadership and work motivation on the performance of State Civil Apparatus (ASN) in government agencies. Data were collected quantitatively by distributing questionnaires to 120 ASN from various divisions. Multiple linear regression analysis was used to see the relationship between variables. The results showed that transformational leadership significantly improved ASN performance, marked by increased initiative, responsibility, and service orientation. Work motivation also had a strong influence on increasing ASN productivity and work quality. The conclusion of this study is that leadership style and internal motivation are two main factors that influence ASN performance. These findings imply that government agencies need to invest in leadership development and motivation enhancement strategies to strengthen the quality of public services.